A two-stage in vivo approach for implanting a 3D printed tissue-engineered tracheal replacement graft: A proof of concept. (April 2022) - Frejo, Lidia; Goldstein, Todd; Swami, Pooja; Patel, Neha A.; Grande, Daniel A.; Zeltsman, David; Smith, Lee P.
Abstract: Objectives: To optimize a 3D printed tissue-engineered tracheal construct using a combined in vitro and a two-stage in vivo technique. Methods: A 3D-CAD (Computer-aided Design) template was created; rabbit chondrocytes were harvested and cultured. A Makerbot Replicator™ 2x was used to print a polycaprolactone (PCL) scaffold which was then combined with a bio-ink and the previously harvested chondrocytes. In vitro : Cell viability was performed by live/dead assay using Calcein A/Ethidium. Gene expression was performed using quantitative real-time PCR for the following genes: Collagen Type I and type II, Sox-9, and Aggrecan. In vivo : Surgical implantation occurred in two stages: 1) Index procedure: construct was implanted within a pocket in the strap muscles for 21 days and, 2) Final surgery: construct with vascularized pedicle was rotated into a segmental tracheal defect for 3 or 6 weeks. Following euthanasia, the construct and native trachea were explanted and evaluated. Results: In vitro : After 14 days in culture the constructs showed >80% viable cells. Collagen type II and sox-9 were overexpressed in the construct from day 2 and by day 14 all genes were overexpressed when compared to chondrocytes in monolayer. In vivo: By day 21 (immediately before the rotation), cartilage formation could be seen surrounding all the constructs. Mature cartilage was observed in the grafts after 6 or 9 weeks in vivo . Conclusion: This two-stage approach for implanting a 3D printed tissue-engineered tracheal replacement construct has been optimized to yield a high-quality, printable segment with cellular growth and viability both in vitro and in vivo .